Rolls Royce strike, Hillington 1943 (1943)
1943 1939-1945 "Rolls Royce strike, Hillington 1943" [HFR0213], 1943 Women workers at the Rolls-Royce plant at Hillington near Glasgow objected to being paid at a lower rate than unskilled men doing the same work. Employers claimed that machinery to build Merlin engines had been simplified for operation by women, although they continued to pay men working the same machines a higher rate. A Court of Inquiry under Lord Wark recommended a new grading system which was agreed by the Amalgamated Engineering Union. However, the women believed the new system would leave 80% of them still on the lowest rate and struck in October 1943 for one week, supported by most men in the plant. Eventually an agreement was reached on a rate for individual machines.